Analisis Efisiensi Inverter pada Grid-Connected 50 KWp Unpam Viktor - Woro Agus Nurtiyanto; Perani Rosyani; Lili Solihin; Wiji Prayogo (Journal of Computer System and Informatics (JoSYC), 2022)
The efficiency of grid-tied inverters in converting electrical energy sourced from solar power plants. The purpose of this study is to find out how efficient the Grid-tied inverter is based on the results of field tests, and it is useful as a reference to determine the performance of an inverter connected to the utility grid. Quantitative research methods with direct measurement techniques use the Seaward PV meter measuring instrument and the IsolarCloud monitoring application and control panel to determine the output power absorbed by the load with the research location in the inverter room on the 7th floor of the Pamulang Viktor University campus. The results show that the highest efficiency is achieved with a value of 98.4% where it can be said that the inverter can convert almost all of the energy produced by solar cells, with an average short circuit current (Isc) 16% greater than the maximum current (Imp) and open circuit voltage (Voc) is 21% greater than the maximum power voltage. The results of the analysis also show that the increase in current has no significant effect on the efficiency of the inverter.